On Traditions Shared by Rabbinic Literature and Slavonic Pseudepigrapha - Ḳuliḳ, Aleksander 1970- (2018)
This article presents motifs shared exclusively by Slavonic minor pseudepigrapha and early rabbinic writings. It is suggested that these cases bear evidence of common early Jewish sources behind both rabbinic and East Christian traditions. This, it is argued, enables a much earlier dating of these rabbinic traditions (otherwise being dated to the period from the third to the twelfth centuries).
Keywords: Apocrypha; Christian; Jewish; Orthodox; Medieval; Motif